Stress and displacement of mini-implants and appliance in Mini-implant Assisted Rapid Palatal Expansion: analysis by finite element method - Pedro Lima Emmerich OLIVEIRA; Kayque Euclides Moreira SOARES; Rafhael Milanezi de ANDRADE; Gabriel Couto de OLIVEIRA; Matheus Melo PITHON; Mônica Tirre de Souza ARAÚJO; Eduardo Franzotti SANT'ANNA (Dental Press Editora, 2021)
ABSTRACT Objective: In this study, simulations were performed by the finite element method (FEM) to determine the tension and displacement in mini-implants and in expander appliance during rapid maxillary expansion, by varying the number and location of the mini-implants. Methods: For the computational simulation, a three-dimensional mesh was used for the maxilla, mini-implants and expander appliance. Comparisons were made on six different Mini-implant Assisted Rapid Palatal Expander (MARPE) configurations, by varying the amount and location of mini-implants. A closed suture was design and received two activations of 0.25 mm, and an open suture had a 0.5-mm aperture that received 20 activations, also of 0.25 mm. Results: For the closed suture, the maximum displacement values in the mini-implants were between 0.253 and 0.280 mm, and stress was between 1,348.9 and 2,948.2 MPa; in the expander appliance, the displacement values were between 0.256 and 0.281 mm, and stress was between 738.52 and 1,207.6 MPa. For the open suture, the maximum displacement values in the mini-implants were between 2.57 and 2.79 mm, and stress was between 5,765.3 and 10,366 MPa; in the appliance, the maximum displacements was between 2.53 and 2.89 mm, and stress was between 4,859.7 and 9,157.4 MPa. Conclusions: There were higher stress concentrations in the mini-implant than in the expander arm. In the simulations with a configuration of three mini-implants, stress overload was observed in the isolated mini-implant. Displacements of the mini-implants and arms of the appliance were similar in all simulations.